Al-Sayyid Muhammad Alawi's Thoughts on The Hadith of Glorifying the Ahl Al-Bayt - Surur, Aziz Miftahus (Millati: Journal of Islamic Studies and Humanities, 2024)
The perception of the equal position of Ahl al-Bayt with society, in general, necessitates the need for research on hadiths recommending glorifying Ahl al-Bayt. This study describes the meaning of hadith in the classical and contemporary eras. This research aims to provide readers with an understanding of the importance of understanding hadith textually and contextually. Al-Sayyid Alawi's theory is intended to help readers comprehend the methodologies employed by classical and modern scholars to practice the Prophet's hadith. Then, the method used in this research is library research. The primary source in this research is the book Manhaj al-Salaf fi Fahm al-Nusus baina al-Nadhariyah wa al-Tatbiq by Al-Sayyid Muhammad Alawi. According to Al-Sayyid Muhammad, the hadith about glorifying the Ahl al-Bayt is a category of authentic hadith. Many narrators narrated this hadith. In interpreting the hadith regarding the recommendation to glorify Ahl al-Bayt, Sayyid Muhammad Alawi is more inclined to the textual meaning. According to him, glorifying Ahl al-Bayt is the obligation of Muslims. Glorifying Ahl al-Bayt is a form of glorification and respect for the Prophet. Ahl al-Bayt, in the Islamic view, has attitudes and conscience like humans in general. They are not equipped with ma'shum characteristics. Wrong attitudes and forgetfulness are two attitudes that are inherent in Ahl al-Bayt as humans in general. There is no contradiction between the hadith's recommendation to glorify Ahl al-Bayt and surah al-hujurat verse 13. Glorifying Ahl al-Bayt is part of Adami's rights. Meanwhile, piety is a right related to Allah. To avoid errors in perception, good judgment is needed in assessing and criticizing Rasulullah's Ahl al-Bayt. Glory and respect are the rights of the Prophet and his family. Respecting the Prophet and Ahl al-Bayt is a characteristic of a pious person.